Imperatives of Negotiation in Managing Covid-19 Vaccination Hesitancy in Nigeria - Daniel Nwanmereni; Oyakemeagbegha Musah (RIRAI Publisher, 2023)
The paradoxical hesitancy to covid-19 vaccination amidst spread of the pandemic, especially the deadly Delta Variant, has remained a source of worry to the global community. Despite assurances of the security and adequacy of the immunizations and the jabs being publicly administered on top Nigerian political hierarchy, covid-19 vaccination has remained controversial in Nigeria. It appears that citizens’ apprehensions about the side effects of the vaccines are yet to be overcome. This study investigated the grounds of Nigerian citizens’ hesitancy to covid-19 vaccination. Among others, the ponder inquired the taking after question: What are factors that underlie Nigerian citizens’ hesitancy to covid-19 vaccination? The quantitative study combined Social Cognitive and Diffusion of Innovations theories as theoretical cornerstone. Survey research design was adopted to study a population of 84, 004, 084 from which a test estimate of 384 respondents was drawn. Research results show that the reported side effects of covid-19 vaccines and citizens’ distrust of Nigerian government and health system were leading factors to covid-19 vaccination hesitancy in Nigeria. NAFDAC’s warning of fake covid-19 vaccines being circulated in Nigeria was also found as a factor that underlies hesitancy to vaccination. The study recommends, among other things, that national and international health authorities should address apprehensions generated by the reported side effects of covid-19 vaccines. It was also recommended that Nigerian political leaders should rise to bridge citizens’ distrust in the government.